Continuous enhancement of educational quality – fostering a quality culture: AMEE Guide No. 147. (2nd January 2023) - Stalmeijer, Renée E.; Whittingham, Jill R. D.; Bendermacher, Guy W. G.; Wolfhagen, Ineke H. A. P.; Dolmans, Diana H. J. M.; Sehlbach, Carolin
Abstract: Internal quality assurance (IQA) is one of the core support systems on which schools in the health professions rely to ensure the quality of their educational processes. Through IQA they demonstrate being in control of their educational quality to accrediting bodies and continuously improve and enhance their educational programmes. Although its need is acknowledged by all stakeholders, creating a system of quality assurance has often led to establishing a 'tick-box' exercise overly focusing on quality control while neglecting quality improvement and enhancement. This AMEE Guide uses the concept of quality culture to describe the various dimensions that need to be addressed to move beyond the tick-box exercise. Quality culture can be defined as an organisational culture which consists of a structural/managerial aspect and a cultural/psychological aspect. As such this AMEE Guide addresses tools and processes to further an educational quality culture while also addressing ways in which individual and collective awareness of and commitment to educational quality can be fostered. By using cases within health professions education of both formal and informal learning settings, examples will be provided of how the diverse dimensions of a quality culture can be addressed in practice.